Physiological and metabolic analysis of Arabidopsis thaliana with low expression of 2-oxoglutarate dehydrogenase subunits - Condori Apfata, Jorge Alberto (2016)
One of the roles of the tricarboxylic acid (TCA) cycle in plants is the production of 2-oxoglutarate (2-OG) required for nitrogen assimilation. In this cycle, isocitrate dehydrogenase and 2-oxoglutarate dehydrogenase (2- OGDH) is involved in synthesis and consumption of 2-OG, respectively. 2- OGDH complex is composed of three subunits responsible for decarboxylation of 2-OG to succinyl CoA with the consequent reduction of NAD + . Notably the 2-OGDH plays an essential role in overall metabolic activity in plants, being limited for respiration and playing important role in the carbon-nitrogen interactions. In Arabidopsis thaliana, E 1 and E 2 subunits are encoded each by two genes. Here, I used two T-DNA insertion mutant lines in each gene encoding E 1 and E 2 subunits of 2-OGDH. For both subunits of 2-OGDH mutant plants exhibited substantial reduction in respiration. The photosynthesis was also altered in plants with low expression of E 1 subunit. Several changes were observed for primary metabolites, with decreased levels of the main nitrogen containing metabolites and increase in metabolites related to carbon metabolism, culminated in alterations of plant growth and seed production. Although both E 1 and E 2 subunits each one are encoded by two genes, they display partial redundant roles in metabolism and plant growth.